Comparison of lower limb muscle activation between slow and fast tempos during the stepping test in young men - Keiji Koyama; Chisa Watanabe; Yusuke Oyama (PLoS ONE, 2025)
The aim of this study was to determine whether and which lower limb muscles contribute to maintaining dynamic balance during the stepping test. Twelve healthy young men performed in-place stepping at tempos of 44 (slow) and 132 (fast) bpm. Vertical ground reaction forces and lower limb muscle activity were recorded using a force plate and a telemetric electromyography (EMG) system, respectively. EMG signals were recorded from the rectus femoris (RF), vastus lateralis (VL), biceps femoris (BF), gastrocnemius medialis (GM), and soleus (SOL) on the right leg. The single-leg support time and the time difference between metronome sound and foot contact at the slow tempo were greater than those at the fast tempo. The impact force at the fast tempo was greater than that at the slow tempo. In the single-leg support phase, the mean EMG signals of the RF, VL, and SOL at the slow tempo were 63%, 17%, and 23% lower, respectively, than those at the fast tempo, whereas the integrated EMG signals of the VL, BF, GM, and SOL at the slow tempo were 171%, 315%, 214%, and 157% greater, respectively. There were no significant relationships among the rate of change in the single-leg support time, the time difference from the slow to the fast tempo, or the rate of change in the EMG activity of each muscle. In the stepping test, movement characteristics associated with tempo were reflected in lower limb muscle activity, while dynamic balance indicators appeared to be influenced by factors other than muscle activation.